2019
DOI: 10.1590/1980-549720190025
|View full text |Cite
|
Sign up to set email alerts
|

Teste de letramento em saúde em português para adultos

Abstract: RESUMO: Introdução: O letramento em saúde é avaliado em diversos países por instrumentos adaptados ao idioma e à cultura locais. O objetivo deste trabalho foi realizar a adaptação transcultural para a língua portuguesa do Brasil e validar o Teste de Letramento em Saúde (TLS), a partir do Test of Functional Health Literacy in Adults (TOFHLA). Método: O TLS, traduzido e adaptado à realidade brasileira a partir do original em inglês, foi administrado a 302 usuários de uma clínica universitária em Santa Catari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 22 publications
1
24
1
6
Order By: Relevance
“…The Functional Health Literacy test used represents a cross-cultural adaptation to the Brazilian Portuguese language of the "Test of Functional Health Literacy in Adults -TOFHLA" of North American origin (11) . This questionnaire includes a set of questions that assess the patient's ability to work with health information that involves numbers and another group of questions that are related to the comprehension of the text (11) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Functional Health Literacy test used represents a cross-cultural adaptation to the Brazilian Portuguese language of the "Test of Functional Health Literacy in Adults -TOFHLA" of North American origin (11) . This questionnaire includes a set of questions that assess the patient's ability to work with health information that involves numbers and another group of questions that are related to the comprehension of the text (11) .…”
Section: Methodsmentioning
confidence: 99%
“…To transform the score on a scale from 0 to 50, the original TOFHLA weighted score table was used, which means that the number of correct answers was multiplied by 2.94 (correction factor) (11) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional health literacy represents the ability to interpret texts and numbers that are usually present in test results or prescriptions, as well as in guidance leaflets (1)(2)(3)(4) . In this way, some tests were developed to measure functional health literacy (2)(3)(4)(5)(6) . Thus, the level of functional health literacy can be classified as adequate or inadequate (4) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study carried out in São Paulo (22) found that low-educated older adults were worse informed, representing a barrier to early access to health services. In a recent study, an association between the factors aging, low education and low functional health literacy was also identified (23) . Consequently, this population is more prone to having trouble understanding the information received at health services, resulting in poorer adherence to the treatments prescribed.…”
Section: Discussionmentioning
confidence: 99%